Evaluating the efficacy of valproic acid in alcohol use disorder: a systematic analysis of clinical trials from ClinicalTrials.gov - Alshehri, Fahad S. (Frontiers in Pharmacology, 2025)
BackgroundAlcohol use disorder (AUD) represents a significant global health burden, characterized by high relapse rates and limited treatment options. Valproic acid, primarily used as an anticonvulsant and mood stabilizer, has been suggested as a potential therapeutic agent for AUD, particularly in patients with coexisting psychiatric conditions. This study systematically analyses clinical trials from ClinicalTrials.gov to evaluate the efficacy of valproic acid in treating AUD.MethodsA systematic search of ClinicalTrials.gov was conducted to identify clinical trials involving valproic acid in the management of substance use disorder (SUD). A total of 3,822 studies related to SUD were initially identified. Screening for anticonvulsant use narrowed this to 96 trials, and four completed studies specifically involving valproic acid and AUD were included in the final analysis. Key outcomes related to relapse rates, substance use reduction, mood stabilization, and withdrawal symptoms were examined.ResultsThe included studies focused on various conditions, including alcohol dependence, bipolar disorder with substance abuse, traumatic brain injury with alcohol use, and medication-overuse headache. Valproic acid demonstrated potential benefits in reducing alcohol consumption, stabilizing mood, and managing withdrawal symptoms in specific subpopulations. However, relapse rates remained high in some trials, indicating limited long-term efficacy. Secondary outcomes showed improvements in psychiatric symptoms, though adverse effects such as sedation and gastrointestinal disturbances were noted.ConclusionValproic acid shows potential as a therapeutic option for managing AUD, particularly in individuals with coexisting psychiatric conditions or complex clinical profiles. While the drug showed some efficacy in reducing substance use and stabilizing mood, the overall impact on long-term abstinence remains uncertain. Further research is needed to better define the role of valproic acid in AUD treatment and to identify patient populations that may benefit most from its use.